Affirming nationality in transnational circumstances: Slovenian coverage of continental franchise sports competitions. (December 2013) - Ličen, Simon; Billings, Andrew C
Sports broadcasts showing national teams frequently have been found to engage in biased and patriotic coverage. However, little is known about the announcers' discourse in club franchise competitions. This study examines discursive framing of nationality within Slovenian broadcasts of international men's basketball and women's team handball matches. Results show that announcers devote Slovenian-based teams just under 60% of all team-related comments. Team affiliation significantly influences explanations of success and failure, as well as personality and physicality descriptions, and 'rival' teams were devoted significantly more positive attribution. Slovenian sports broadcasters emphasized national identity through differentiating team identification, overt cheering for Slovenian-based teams, and influencing the way results and performances are interpreted. Nation-centric discourse is thus applied even in professional sports involving city franchises, as club teams are perceived as year-round substitutes for national teams. This likely derives from the role attributed to sports franchises in federal Yugoslavia. In Slovenia, televised promotion of nationhood nurtures a sense of national identity in a country that lacks a long-standing tradition of sovereignty. Public service broadcasters inaccurately perceive this approach as universal.